﻿Socioeconomic impacts on medication adherence among patients with hypertension: A multicentre cross-sectional study in Lombok, Indonesia - Adji Prayitno Setiadi; Sari Widiyastuti; IGA Dewi Mariati; Bruce Sunderland; Yosi Irawati Wibowo (Pensoft Publishers, 2022)
Socioeconomic impacts on adherence are understudied, particularly in disadvantaged areas. This study aimed to evaluate socioeconomic factors on medication adherence among patients with hypertension in Lombok, Indonesia. A cross-sectional survey was conducted in all six public hospital outpatient clinics in Lombok in 2017. Data was obtained using a validated questionnaire to which the Morisky Green Levine Adherence Scale (MGLS) questionnaire was used to assess medication adherence. Binary logistic regression was performed to determine independent socioeconomic associations. A total of 693 patients with hypertension were included (response rate 84%). The majority had low adherence (76.2%). Significant independent associations were reported between setting and education with adherence (rural versus urban setting: odds ratio 3.54, p<0.001; primary versus university level education: odds ratio 5.39, p<0.001). Socioeconomic associations provide some basis for the development of patient and population-based interventions to improve adherence among patients with hypertension in Indonesia, particularly in disadvantaged areas.